Exploring the Current Applications and Future Implications of Artificial Intelligence in Public Health Dentistry: A Narrative Review - Tanushri Mahendra Dalvi; Rajeshri Kotwadekar; Shrivardhan R Kalghatgi; Priyanka Paul Madhu; Priyanka Methildeotare (Journal of Clinical and Diagnostic Research)
Artificial Intelligence (AI) is transforming healthcare at a rapid rate by enhancing disease prevention, diagnosis, treatment planning and management of health systems. AI technologies such as machine learning, deep learning, and natural language processing have been able to show an enormously huge scale capacity for improvement in oral health outcomes at the population level, particularly among disadvantaged groups. AI based applications in preventive dentistry can identify high risk individuals for dental caries, periodontal infections and oral cancer to allow targeted dental care. Deep learning algorithms can also be applied in imaging diagnostics and dental care can be personalised using patient’s history, habits and genetics. AI applications can also be utilised in epidemiologic surveillance for analysis of health-related information in forecasting disease patterns and drafting evidence based public health policies. AI can enhance dental education and training of new dental professionals through simulation-based education and intelligent tutoring systems. Administrative efficiency can also be achieved using AI based management software for patient scheduling, billing, and resource management which can reduce the workload of the clinician and enhance the functioning of health system. Inspite of the widespread applications of AI in dental public health, ethical issues related to data security, unequal access to technology and regulatory policies need to be addressed. Transparency in AI usage, accountability and equitable incorporation of AI in health systems are required. With a focus on diagnostic tools, epidemiological monitoring, individualised care, and health system management, this review article attempts to investigate the various uses of AI in public health dentistry. In the present review article, future prospects for AI in the public health dentistry field are explored, as well as its possible advantages and difficulties.